2019
DOI: 10.1016/j.heliyon.2019.e02060
|View full text |Cite
|
Sign up to set email alerts
|

Li2TiO3/Ni foam composite as high-performance electrode for energy storage and conversion

Abstract: Li 2 TiO 3 /Ni foam composites were prepared by a solid-state reaction process. They crystallized in the monoclinic Li 2 TiO 3 structure with C 2/ c space group. SEM images show that the Li 2 TiO 3 particles are monodispersed crystallites of average size 49 nm, infused into porous scaffold Ni foam. As an anode in lithium battery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Open-cell metallic foams are regarded as a versatile engineering material, as they can be used in various applications including heat exchangers, energy absorbers, filters, porous electrodes, fluid mixers, and so on [ 1 , 2 , 3 ]. Their unique properties, such as high porosity (75–95%), high surface area (up to 10,000 m 2 /m 3 ), high intrinsic solid conductivity, and rigorous surface texture, have made them an excellent choice for catalyst supports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Open-cell metallic foams are regarded as a versatile engineering material, as they can be used in various applications including heat exchangers, energy absorbers, filters, porous electrodes, fluid mixers, and so on [ 1 , 2 , 3 ]. Their unique properties, such as high porosity (75–95%), high surface area (up to 10,000 m 2 /m 3 ), high intrinsic solid conductivity, and rigorous surface texture, have made them an excellent choice for catalyst supports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because the electrical current mainly flows through the 3D Ni foam due to its higher electrical conductivity compared to Li metal. 27,31,32 Consequently, the 3D Ni foam plays a critical role in reducing the current density and enhancing the electrical conductivity of the 3DLM electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In practice, a relatively smaller current value (<1 mA cm –2 ) is observed in the Li-metal region of the 3DLM electrode compared to the conventional 2DLM electrode. This is likely because the electrical current mainly flows through the 3D Ni foam due to its higher electrical conductivity compared to Li metal. ,, Consequently, the 3D Ni foam plays a critical role in reducing the current density and enhancing the electrical conductivity of the 3DLM electrode.…”
Section: Resultsmentioning
confidence: 99%
“…15 Early reports on β-Li 2 TiO 3 showed that only at extremely low C-rate can low specific capacity in the range of 15–60 mA h g −1 be realised, accompanied by severe capacity fading afterwards. 16–19 Although β-Li 2 TiO 3 /Ni exhibited significantly improved electrochemical performance in a recent report by Lakshmi-Narayana et al , 20 they found that it was the high electronic conductivity and high effective surface area of the porous Ni foam substrate that contributed to this improvement. Therefore, β-Li 2 TiO 3 is often combined with other cathode/anode materials to stabilize its structure during cycling or enhance the ionic diffusion coefficient.…”
Section: Introductionmentioning
confidence: 97%